PENDIDIKAN KARAKTER BERBASIS BUDAYA LOKAL “ RORI LAKO” PADA PEMBELAJARAN DI SEKOLAH DASAR - Lina, Virgilius Bate; Bhoki, Maria Fransiska; Umar, R.A Yunita; Koban, Emerensiana Sabu; Olu, Antonia Febriani (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
The problem of this research is how is the rori lako tradition in relation to observing the relationship of cultural values ​​of local wisdom to character education in elementary social studies learning?. The type of research conducted is qualitative research. The location of this research was carried out in Loa Village, Soa District. Informants taken in this study, namely 1 traditional elder as key information, 1 social studies learning teacher and 1 community leader were designated as supporting information. Data collection techniques used in this study were interviews and observation. From the results of the study, it can be concluded that the value of the rori lako tradition in relation to the cultural values ​​of local wisdom on character education in social studies learning, which occurred in Loa Village is character education and the cultural values ​​of local wisdom actually both aim to instill values noble values ​​that will produce good human beings in the future. Therefore, character education based on the cultural values ​​of local wisdom is very appropriate to be applied in the social studies learning process. The results of the study found the cultural values ​​of local wisdom in social studies learning, including religious values, hard work values, and mutual cooperation values.